A systematic review of treatments for Impulse Control Disorders and related behaviours in Parkinson׳s disease. Issue 3 (28th February 2015) - Tanwani, Puja; Fernie, Bruce A.; Nikčević, Ana V.; Spada, Marcantonio M.
Abstract: Impulse Control Disorders (ICDs) are a set of behaviours characterised by impulsivity despite known harm. Related to ICDs is the dopamine dysregulation syndrome (DDS), which is characterised by an addiction-like consumption of dopaminergic medication and punding. These behaviours all have an increased prevalence in Parkinson׳s disease (PD). The aim of this review is to identify treatments available for patients suffering from ICDs, DDS and punding in PD. Searches of The Cochrane Controlled Trials Register, Embase, Medline and PsychInfo were conducted, using the entire timescale available. Seven out of the 688 papers retrieved met the inclusion criteria and were considered in this systematic review. One class I study, one class II study, and five class IV studies were identified. All studies demonstrated a positive effect on ICDs in PD. Research in this field is still in its early stages. At present, there is insufficient evidence to recommend any treatment over another. There is a need for more methodologically robust research, using larger, more generalisable samples, randomisation and meaningful follow-up periods. In addition, the use of a validated outcome measures should be implemented in future research efforts. Highlights: First systematic review on treatments for Impulse Control Disorders and related behaviours in Parkinson׳s Disease. There is insufficient evidence to recommend any treatment over another. There is a need for more methodologically robust research.